Herpetic Stromal Keratitis following Selective Laser Trabeculoplasty - Chadha, Nisha (Case Rep Ophthalmol Med, 2016)
This is a case report describing two cases of disciform corneal edema following uncomplicated selective laser trabeculoplasty (SLT) thought to be secondary to herpes simplex virus (HSV) given the presence of a dendrite, decreased corneal sensation, corneal thinning, and response to therapy with oral and topical antivirals. Corneal edema after SLT treatment has been reported before, but the etiology has been unclear. Our cases highlight HSV as a likely etiology, which may help with prevention and better management of such cases in the future.